“Pelaksanaan Metode Sorogan dalam Meningkatkan Kualitas Baca Kitab Kuning Santri (Study Kasus di Pondok Pesantren Putri Zainul Hasan Genggong Pajarakan)” - INZAH; Mujibus Sailin (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2021)
Abstract Pesantren as an Islamic educational institution selectively aims to make its students as independent human beings who are expected to become leaders of the people in the direction of God's pleasure. To achieve this goal, the pesantren teaches the compulsory books (Kutubul Muqarrarah) as textbooks known as the yellow book. The problem of education today in various countries is seen as a very extraordinarily difficult problem. People who want to build and try to improve the state of the world certainly say that education is the key and without that key they will fail. Sorogan learning in Zainul Hasan Genggong Islamic Boarding School uses two models, namely formal education and non-formal education. Non-formal education carried out within the Islamic boarding school itself which teaches only religious education using methods such as: the wetonan method, sorogan, deliberation, memorization, demonstration/practice of worship. Sorogan learning at the Zinul Hasan Genggong Islamic Boarding School Pajarakan is carried out in 1 (one) class divided into several groups and each group consists of 15-20 people with one teacher in each group. Sorogan learning is carried out in a room that is given boundaries or divided into plots, this is done so that in the teaching and learning process there is no communication between one group and another. With the sorogan method, this makes students memorize the rules. - the method of reading the yellow book, such as shorrof and nahwu. Students can express these principles and can implement or practice them in daily learning at the Zainul Hasan Genggong female Islamic boarding school. Keywords: Sorogan, Yellow Book, Zainul Hasan Genggong